A aplicação de resina consolidante e a arqueofauna nas práticas funerárias do sítio arqueológico Justino, Canindé de São Francisco, Sergipe, Brasil - Cardoso, Carlos Eduardo (2015)
In two burials found in the archaeological site of Justin were highlighted human subjects and animals interred, concomitantly, in the mortuary context of prehistoric culture of the Xingó region, between the states of Sergipe and Alagoas. After the archaeological intervention, the skeletons remained in plaster cocoons until the time to be studied. In the second half of the 1990s there was an application of a consolidating substance for morphological preservation of skeletons 119 and 166, whose burials have indicated the presence of animals probably interred in human graves on purpose. This fauna archaeological found in the funerary context of past groups, showed that both the individual 119, which evidenced a ferret (Galictis cuja), as the 166, found with a bird, possibly prey, associated, offered evidence linked funeral activities the symbolic activities, in other words, that culture had a sense of abstractly fauna in which individuals could hold a different social status and the animals would have functions such as psychopomp.